Mutations in the Gene DNAJC5 Cause Autosomal Dominant Kufs Disease in a Proportion of Cases: Study of the Parry Family and 8 Other Families - Velinov, Milen; Dolzhanskaya, Natalia; Gonzalez, Michael; Powell, Eric; Konidari, Ioanna; Hulme, William; Staropoli, John F.; Xin, Winnie; Wen, Guang Y.; Barone, Rosemary; Coppel, Scott H.; Sims, Katherine; et al. (PLOS ONE, 2012)
Background The Neuronal Ceroid Lipofuscinoses (NCL) comprise at least nine progressive neurodegenerative genetic disorders. Kufs disease, an adult-onset form of NCL may be recessively or dominantly inherited. Our study aimed to identify genetic mutations associated with autosomal dominant Kufs disease (ADKD). Methodology and Principal Findings We have studied the family first reported with this phenotype in the 1970s, the Parry family. The proband had progressive psychiatric manifestations, seizures and cognitive decline starting in her mid 20 s. Similarly affected relatives were observed in seven generations. Several of the affected individuals had post-mortem neuropathological brain study confirmatory for NCL disease. We conducted whole exome sequencing of three affected family members and identified a pLeu116del mutation in the gene DNAJC5, which segregated with the disease phenotype. An additional eight unrelated affected individuals with documented autosomal dominant or sporadic inheritance were studied. All had diagnostic confirmation with neuropathological studies of brain tissue. Among them we identified an additional individual with a p.Leu115Arg mutation in DNAJC5. In addition, a pAsn477Ser change in the neighboring gene PRPF6, a gene previously found to be associated with retinitis pigmentosa, segregated with the ADKD phenotype. Interestingly, two individuals of the Parry family did report visual impairment. Conclusions Our study confirmed the recently reported association of DNAJC5 mutations with ADKD in two out of nine well-defined families. Sequence changes in PRPF6 have not been identified in other unrelated cases. The association of vision impairment with the expected PRPF6 dysfunction remains possible but would need further clinical studies in order to confirm the co-segregation of the visual impairment with this sequence change.